Evaluation and grading of Kayser–Fleischer ring in Wilson disease by Scheimpflug camera. Issue 4 (July 2021) - Degirmenci, Cumali; Palamar, Melis
Purpose: Evaluation the anterior segment parameters of Wilson disease patients with Kayser–Fleischer ring, the diagnostic power of Scheimpflug imaging for Kayser–Fleischer ring and suggest a scoring system. Materials and Methods: A total of 44 eyes of 22 Wilson disease patients with Kayser–Fleischer ring and 40 right eyes of 40 healthy age matched subjects were enrolled to the study. Serum ceruloplasmin and urine copper/24 hours levels were recorded. Anterior segment parameters including steep and flat keratometry, corneal thickness at central, 2, 4, 6, 8 and 10 mm, anterior chamber angle width, volume and depth, corneal volume, pupillary diameter were evaluated by Scheimpflug imaging. Images of cornea were scored according to Kayser–Fleischer ring size. Results: Serum ceruloplasmin level was below 10 mg/dL in 17 patients and was 12, 18.5, 20, 22, 37 mg/dl in the remaining five patients. Urinary copper/24 hours was 249.55 ± 304.14 (23–1050) µg/day. Central corneal thickness and corneal thickness at 2 mm were statistically different ( p values 0.02, 0.04, respectively). Scheimpflug images apparently showed Kayser–Fleischer ring as a hyper-reflective band at the corneal endothelial surface. Kayser–Fleischer ring in 24 eyes was grade 1, 16 eyes were grade 2 and 4 eyes were grade 3. Conclusion: Scheimpflug imaging seems to be a helpful diagnostic tool for detecting and grading the Kayser–Fleischer ring. Corneal thickness in Wilson disease patients with Kayser–Fleischer ring tends to be higher, so that the possible affection in corneal thickness should be kept in mind for clinical evaluation of these patients.